The Effect of Acid Concentration (H2SO4) on the Yield and Functional Group during Lignin Isolation of Biomass Waste Pulp and Paper Industry - Slamet Priyanto; Anansya Putri Intan; Bambang Rianto; Tutuk Djoko Kusworo; Bambang Pramudono; Edi Untoro; Puspa Ratu (Reaktor, 2019)
Declining oil production in Indonesia lately has been much discussed by industrial practitioners, especially from the petroleum industry. The decrease is due to the age of old drilling wells with high water cut (> 90%), so it is necessary to pursue a production method that can increase the production of these old wells. The EOR (Enhanced Oil Recovery) method is one way of extracting oil from oil wells that cannot be further retrieved by injecting materials that are not in the reservoir. One ingredient that can be injected is Sodium Ligno Sulfonate (SLS) surfactant derived from lignin. Lignin was obtained from the lignin isolation process from Black Liquor, which in this study came from the pulp and paper mill waste of PT. Indah Kiat, Pekanbaru, Sumatra, Indonesia. This study aims to determine the effect of variations in H2SO4 concentrations (concentrations of 15%, 20%, 25%, 30% w/w) on the yield of lignin isolation results, and to compare the functional groups between dirty lignin, clean lignin, and pure lignin using FT-IR. Based on the research results, it was found that the best lignin is lignin with an H2SO4 concentration of 20%, with the highest yield and the color of lignin produced tends to be similar to pure lignin. In addition, it was found that the peak of the net lignin group had more similarity with commercial lignin compared to crude lignin. Keywords: Lignin, Black Liquor, Enhanced Oil Recovery (EOR), FTIR